Advances in sympathetic nerve recording in humans - Elisabeth eLambert (Frontiers in Physiology, 2012)
Sympathetic nerve recording is commonly assessed by measuring the firing activity of a number of neurones. While the estimation of overall sympathetic nervous activity using this multiunit recording approach has advanced our understanding of sympathetic regulation in health and disease no information is gained regarding the underling mechanisms generating the bursts of sympathetic activity. The introduction of single-unit recording has been a major step forward, enabling the examination of specific sympathetic firing patterns in diverse clinical conditions. Disturbances in sympathetic nerve firing, including high firing probabilities, high firing rates or high incidence of multiple firing, or a combination of both, may have clinical implications with regards to the development and progression of target organ damage. Understanding the mechanisms and consequences of specific firing patterns would permit the development of therapeutic strategies targeting these nuances of sympathetic overdrive.